Diagnostic and prognostic value of sex- and age-specific cutpoints for high-sensitivity Troponin T in non-ST-elevation acute coronary syndrome - Widera, Christian; Giannitsis, Evangelos; Müller-Hennessen, Matthias; Reimann, Ines; Guba-Quint, Anja; Marquardt, Ivonne; Bethmann, Kerstin; Meyer, Sven (International journal of cardiology, 2019)
Introduction - Sex- and age-specific high-sensitivity Troponin T (hs-cTnT) cutpoints for the diagnosis and prognosis in acute coronary syndromes are not well established. We evaluated the use of such dichotomous thresholds for calculation of the GRACE score. - Methods - We analyzed a retrospective cohort study of 1146 patients with non-ST-elevation acute coronary syndrome (NSTE-ACS). Sex-dependent hs-cTnT cutpoints comprised 15.5ng/L for men and 9.0ng/L for women, while the sex-/age-specific cutpoints comprised 17ng/L for 50-64-year-old men and ≥65-year-old women, 31ng/L for ≥65-year-old men and 14ng/L for the remainder of patients. - Results - For the diagnosis of NSTEMI using sex-specific hs-cTnT cutpoints, in women, the positive likelihood ratio (LR+) was 2.04 (1.68-2.47) while in men, the negative likelihood ratio (LR−) was 0.05 (0.04-0.07). Using sex-/age-specific hs-cTnT cutpoints, in ≥65-year-old women the LR− was 0.09 (0.06-0.15), in 50 to 64-year-old men the LR− was 0.08 (0.04-0.13) while in ≥65-year-old men the LR− was 0.32 (0.28-0.37). Sex-specific hs-cTnT cutpoints achieved an NRI of −0.020 (95% CI, −0.101-0.118) for women and 0.030 (95% CI, −0.013-0.079) for men, and the sex-/age-specific hs-cTnT cutpoints achieved an NRI of 0.061 (95% CI, −0.019-0.132) for women and 0.021 (95% CI, −0.062-0.108) for men, while net benefit and clinical utility were highest for women using the sex-/age-specific hs-cTnT cutpoints. - Conclusions - Sex-dependent hs-cTNT cutpoints imply increasing diagnostic sensitivity for women at the cost of specificity. Considering age for hs-cTNT cutoffs slightly improves risk reclassification, although the overall gain in terms of the clinical management appears negligible.
Available online 11 October 2018
Gesehen am 09.05.2019